Onomastyczne tropy dekadentyzmu. Nazwy własne w Bez dogmatu Henryka Sienkiewicza - Rejter, Artur (Acta Universitatis Lodziensis. Folia Linguistica, 2016)
Proper names should be recognized as a significant factor of a literary character and in broader perspective of bringing closer the novel problems. The main novel character, Leon Płoszowski, percepts and sense the world through the self-analysis and analysis of the reality surrounding him. Proper names above all emphasize two features: erudition and cosmopolitism of the novel character. His formation and contact through the years with high culture do not help him to put the world – both: one inside and one outside him – in order, but all of this remains a stigma in a form of association everything with art, literature, philosophy etc. It is confirmed in the novel by numerous proper names. The fact that proper names in basic for Leon Płoszowski characteristics places in the novel apply mostly to the past, causes that they form sort of „onomastic museum”.